1993
DOI: 10.1080/0028825x.1993.10419503
|View full text |Cite
|
Sign up to set email alerts
|

A randomisation test of the null hypothesis that two cladograms are sample estimates of a parametric phylogenetic tree

Abstract: Cladograms for the same group of taxa deri ved using different datasets often agree extensively but are seldom identical. This disagreement may be due to the fact that cladograms are sampling estimates of the true phylogeny and as a result may differ only because of sampling erro~. A protocol is proposed to test the null hypothesis that two trees estimate the true or parametric phylogeny and are no more different than would be expected due to sampling error. In the event that the null hypothesis is rejected, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 18 publications
2
104
0
1
Order By: Relevance
“…However, as other authors have argued (31,34), evolutionary trees estimated from a single gene should be treated with caution. The degree to which lateral transfer of genetic material has occurred and the effects of ancestral polymorphism and selection cannot be readily estimated.…”
Section: Resultsmentioning
confidence: 99%
“…However, as other authors have argued (31,34), evolutionary trees estimated from a single gene should be treated with caution. The degree to which lateral transfer of genetic material has occurred and the effects of ancestral polymorphism and selection cannot be readily estimated.…”
Section: Resultsmentioning
confidence: 99%
“…This use of consensus analysis is inappropriate for two reasons (Mirkin et al, 1995): first, consensus methods cannot accommodate differing sets of terminal entities (Page, 1996), such as arises from gene trees exhibiting polymorphism or simply from gene trees with sequences sampled from different species; and second, consensus trees do not represent real biological events. Rodrigo et al (1993) have advocated a sequenceexcision procedure, wherein problem sequences are excised, the data sets tested for homogeneity, and the procedure repeated until the null hypothesis that two data sets represent character samples from the same phylogeny cannot be rejected. Excising sequences, however, may not be the best way to accommodate gene tree conflict (see below).…”
Section: Inferring Species Trees From Gene Treesmentioning
confidence: 99%
“…This is a procedure where the sequence data for a single taxon are removed from both data sets to remove possible misinformative data (Rodrigo et al, 1993). This procedure was performed by first generating a 50 % majority rule consensus tree, from the equally parsimonious trees generated in the above topology analysis, for each of the ITS sequence data sets.…”
Section: Congruence Studies Of Its1 and Its2 Sequence Datamentioning
confidence: 99%
“…Following this, a test based on that of Rodrigo et al (1993) was performed to identify if differences observed in the topologies of the phylogenetic trees generated from the ITS1 and ITS2 data sets were significantly different or the result of sampling error. MP trees were generated from both the ITS1 and ITS2 sequence data sets using the seven taxa common to both data sets (MTM, M1057, GJS90-90, TR112, US1, HEND and TR90), as well as the four outgroups mentioned previously.…”
Section: Congruence Studies Of Its1 and Its2 Sequence Datamentioning
confidence: 99%